Influence of infrastructure financing on financial sustainability of water service providers in Kenya - Крістін Мавія Юліус; Тимофі Ч. Океч (European Journal of Management Issues, 2021)
Purpose: To establish the influence of infrastructure financing on financial sustainability of water service providers (WSPs) in Kenya.